Volumetric histogram-based analysis of cardiac magnetic resonance T1 mapping: A tool to evaluate myocardial diffuse fibrosis. (February 2021) - Di Renzi, P.; Coniglio, A.; Abella, A.; Belligotti, E.; Rossi, P.; Pasqualetti, P.; Simonelli, I.; Della Longa, G.
Highlights: Cardiac magnetic resonance is a powerful tool to evaluate diffuse fibrosis. Volumetric histogram-based analysis can precociously detect diffuse fibrosis. Silent heart diseases would benefit from T1 mapping histogram-based analysis.